"A Theory of the Art of Writing": Virginia Woolf's Aesthetics from the Point of View of Her Critical Essays. Issue 8 (17th November 2017) - Nünning, Vera
ABSTRACT: Attempts to explore Virginia Woolf's theory of aesthetics are usually based on or aimed at a consideration of her novels. However, a careful analysis of her essays allows us to trace cornerstones of her aesthetics, which—though not amounting to a rigid formal framework—are surprisingly coherent. While her ideas about "the art of writing" developed throughout her lifetime, and although the emphasis shifts, it is possible to identify some major aesthetic principles upon which she elaborated in only a handful of theoretical essays, but which nonetheless underpin both the practice and the theory of her literary criticism. Examining the connections between Woolf's beliefs about aesthetics, it becomes possible to place her thoughts about modernist modes of writing in the context of her overarching framework of ideas concerning literature and literary change. For Woolf, writing was a method of communication, and some key characteristics of her aesthetics include writers' visions, formal unity, impersonality and the cultural embedding of literature. Considering not only cultural circumstances but also readers' expectations as possible obstacles that can distract writers and impair their work, Woolf wrote hundreds of essays trying to convey her ideas about the "art of writing" to common readers.